A Contextual Interpretation of Disability Inclusion in 2 Samuel 9 and the Bamasaaba of Eastern Uganda - Simon Masiga; Helen N. Nkabala (The Thinker)
Disability inclusion among African communities is shaped by African religious discourse on disability, which influence the perceptions of the society. This article provides a contextual reading of disability inclusion in 2 Samuel 9 and among Bamasaaba of Eastern Uganda. The authors argue that although inclusive communities are affirmed in both Old and New Testaments, some oppressive and discriminative interpretations of biblical texts still exist. It explores how interpretation of disability in 2 Samuel 9 and among Bamasaaba can transform religious perceptions on disability inclusion. Through interpretive hermeneutical approach and historical-critical methods, the article establishes that aspects of identity, social status and perception as interpreted in 2 Samuel 9 correspond to how Bamasaaba construct disability phenomenon in their socio-religious contexts. Contextual interpretation of disability inclusion is significant for the liberation, inclusion, and empowerment of people with disability to actively participate in society. Using African disability hermeneutics, biblical texts can be interpreted to transform the negative attitudes, theological views and religious perceptions on disability. Arguably, transforming the religious perceptions is necessary to removing barriers to inclusive religious and social participation of persons with disability.